Due Lari in bronzo da Veleia (ACME, 2023)
The aim of this paper is to examine two bronze Lares found in the excavations of Veleia and kept in the local Antiquarium. The two statuettes have some iconographic peculiarities: one seems to belong to a rare type of Compitales with rhyton and kantharos; the other, iconographically close to the Lar Famliaris, has the attributes placed in a reverse position. In this study I try to contextualize it in the Cisalpine small bronzes tradition, and to deepen the knowledge about these two rare iconographies.